Memahami Peran Platfrom Jejaring Sosial Media dalam Mengatasi Tantangan Perbankan Syariah - Widya Anggraini, Kirana; Hak, Nurul; Sumarni, Yenti (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2025)
Islamic banking in Indonesia continues to experience significant growth, but still faces various challenges, especially in competition with fintech and conventional banks, compliance with sharia principles in digital innovation, and low customer digital literacy. Social networking platforms have great potential to help overcome these challenges by increasing financial inclusion, building trust, and expanding the marketing reach of Islamic banks.